How Korean Venture Capitals Invest In New Technology Ventures - Youngkeun Choi (Journal of Entrepreneurship, Management and Innovation)

(untitled)
In the entrepreneurship field, this study examines what kinds of external endorsements are helpful for venture capitals investment and the growth of new technology ventures in developing countries. This study uses the signalling theory and the methodologies of multiple regression and survival analysis with the panel data of the ventures in Korea. In the results, collaboration with business groups and certification of government are positively influential in attracting venture capitals’ investment, which accelerate the growth of new technology ventures. The practical implication for entrepreneurs is that they need to obtain the endorsement from business groups and governments strategically.